FORMATION OF DEONTOLOGICAL COMPETENCE IN PREPARING UNIVERSITY STUDENTS FOR PEDAGOGICAL ACTIVITY - Sadikova Shoira Odeldjanovna (Galaxy International Interdisciplinary Research Journal, 2024)
The article examines the methodological, methodological and organizational-pedagogical conditions for the formation of deontological competence in the process of preparing university students for teaching activities. Also, the article outlines the structure and content of deontological competence, organizational forms, types and methods of training in the classroom and outside the classroom in the formation of deontological competence.